Restructuring and Rebranding Public Universities in Nigeria for Global Competitiveness: the Emerging Issues - ABARI, A.O.; GABADEEN, W.O.; HAUWA, K. MUHAMMAD (International Journal of Educational Management, 2021)
The relevancy and employability of the graduates of Nigerian public universities and their ability to compete with their counterparts globally in a world where knowledge, technology and innovation are constantly advancing and changing the operations of socio-economic and political systems locally, regionally and internationally. This paper therefore advocates for restructuring and rebranding of Public Universities in Nigeria for global competitiveness and discusses the emerging issues. The paper brings to fore critical emerging issues for restructuring and rebranding public universities in Nigeria with action plans, deliverables and 2030 Agenda setting is articulated. The issues include; leadership for strategic management, ownership and autonomy, staff and students, curriculum and academics, funding and financial management, physical infrastructure development and facilities management, regulatory/quality assurance and external relations, general management, financial framework and strategic planning. However, the dwindling financial resources accruing to the university sector from the public treasury was noted with dismay and therefore the paper recommends a paradigm shift from public-funded to public-assisted institutions as basis for determining appropriate financial framework for sustainable university education in Nigeria. This framework shall be articulated for further policy and legislative actions aimed at enhancing global visibility of Nigerian Universities and production of universally acceptable graduates of the system contributing meaningfully to Nigeria economy in particular and global economy in general in line with 2030 Agenda.